Bidah Pomegranate Landrace: Chemical Composition, Antioxidant, Antibacterial, and Anticancer Activity - Abdalrhaman M. Salih; Nada M. Alattas; Qasi D. Alsubaie; Saheed O. Anifowose (Life)
Pomegranate (Punica granatum L.) belongs to the Punicaceae family and is native to Central Asia; yet, it has a wide geographical distribution globally, reflecting its adaptation to different climatic conditions. Pomegranate is among the oldest and most significant cultivated crops, thriving extensively in tropical and subtropical climates. Besides its nutritional uses, pomegranate has been employed in traditional medicine for treating various diseases, including cancer prevention, antimicrobial activity, male infertility, ulcers, and diarrhea. The Bidah pomegranate cultivar is known for its unique sweet taste and high productivity yield. However, there is limited knowledge about its nutritional composition and medicinal value. Therefore, this study aimed to evaluate the functional potential of Bidah pomegranate in terms of its phytochemicals, antioxidant capacity, antibacterial, and anticancer activity. Different analytical techniques were used to investigate the chemical composition and antioxidant properties of Bidah pomegranate. Moreover, the biological activity of shoot and callus of Bidah pomegranate cultivar was assessed against Escherichia coli (E. coli), Staphylococcus aureus (S. aureus), and the colorectal cancer cell line (CaCo-2). Gas chromatography/mass spectrometry (GC/MS) analysis of the shoot and callus extracts revealed about 17 and 18 phytochemical compounds, respectively. Phenolic quantification showed that pomegranate materials contained high amounts of phenolic content. Additionally, Bidah pomegranate cultivar possesses high antioxidant activity with a low half-maximal inhibitory concentration (IC50) value. Furthermore, the pomegranate extract showed promising results with human pathogenic bacteria (E. coli and S. aureus), especially against S. aureus and the colorectal cancer cell line (CaCo-2). The findings of this study support the traditional use of pomegranate in folk medicine and highlight its potential for further exploration as a source of therapeutic agents.